Serum C-reactive protein concentration in preeclamptic women: Effect on pregnancy outcome (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Preeclampsia is a multisystem disorder of unknown etiology characterized by development of hypertension to the extent of 140/90 mm of Hg or more with proteinuria after the 20th gestational week in a previously normotensive and non protein uric women. According to the National High blood presure Working group (NHBPEP) and American college of obstetricans and Gynecologiests (ACOG) hypertension in pregnancy is defined as a diastolic blood pressure of 90 mm Hg or higher after 20 weeks of gestation in a woman with previously normal blood pressure (NHBPEP, 2000; ACOG, 2002). If the disease is allowed to progress to the HELLP syndrome or eclampsia, maternal morbidity and mortality increases. The majority of perinatal losses are related to placental insufficiency, which causes intrauterine growth retardation, prematurity associated with preterm delivery, or abruptio placentae. Objectives: This study tried to explore the effect of serum C reactive protein concentration in preeclamptic women and its effect on pregnancy outcome.Methods: This case control study included 60 third trimester pregnant women (30 normotensive and 30 preeclamptic) who attended Department of Obstetrics and Gynaecology, BIRDEM and DMCH, during July 2009 and June 2010. Estimation of serum C reactive protein (CRP) concentrations was done by liquid phase immunoprecipitation assay and turbulometry at DMC.Results: Mean (±SD) age showed no significant difference between groups; however, BMI, SBP, DBP and CRP were significantly (P